Gastrointestinal ischemia: endoscopic findings in the context of vascular insufficiency - Hourneaux De Moura, Diogo Turiani (2019)
Gastrointestinal ischemia may result from different causes: hemodynamic shock, thromboembolism, endoscopic or surgical complications, among other causes. Its symptoms are pain, vomiting, bleeding and bloating. Endoscopic findings are pale or blackened mucosa, and exudative and confluent ulcerative lesions. This paper aims to report a case of gastroduodenal ischemia associated with hemodynamic shock and disseminated intravascular coagulation (DIC). This is a case of a 56-years-old male with multiple comorbidities, presenting with refractory septic shock and DIC. He underwent an upper gastrointestinal endoscopy (UGE) for investigation of melena, which revealed an extensive deep and exudative gastric ulcer, associated with edematous purplish duodenal mucosa. Due to the severity of the underlying condition, the patient evolved to death, evidencing septic shock as cause of death. Gastroduodenal ischemia is associated with a poor prognosis, in which early diagnosis by UGE is fundamental to guide potential interventions.